1985
DOI: 10.1007/bf00117589
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spermidine synthesis inhibitors on in-vitro plant development

Abstract: The spermidine synthesis inhibitors methylglyoxal bis-(guanylhydrazone) (MGBG) and dicyclohexylammordum sulfate (DCHA) were found to reduce growth and embryogenesis in wild carrot cultures. Cellular polyamine levels were also affected by the inhibitors, with spermidine levels being especially reduced by DCHA. Similarly, MGBG reduced organogenetic development of shoots on excised aspen hypocotyls. These data suggest that the polyamines, especially spermidine, play an important role in the growth and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0
3

Year Published

1988
1988
1996
1996

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 21 publications
2
12
0
3
Order By: Relevance
“…Recent evidence suggests a possible role for polyamines, especially Spd, in reproductive differentiation in various organisms (2,7,10,11,15 eluted with a protein fraction having a molecular mass in excess of 45,000 in oat and petunia protoplasts (14). Because there was a large difference in the relative molecular mass in the polypeptides from tobacco thin-layer culture and oat and petunia protoplasts, a need exists to establish unambiguously the size of proteins that are labeled by Spd, as was also suggested by Mizrahi et al (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests a possible role for polyamines, especially Spd, in reproductive differentiation in various organisms (2,7,10,11,15 eluted with a protein fraction having a molecular mass in excess of 45,000 in oat and petunia protoplasts (14). Because there was a large difference in the relative molecular mass in the polypeptides from tobacco thin-layer culture and oat and petunia protoplasts, a need exists to establish unambiguously the size of proteins that are labeled by Spd, as was also suggested by Mizrahi et al (14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests a possible role for polyamines, especially Spd, in reproductive differentiation in various organisms (2,7,10,11,15). Application of exogenous Spd causes floral initiation in cultures which would otherwise form vegetative buds.…”
mentioning
confidence: 99%
“…Hydrolysis of this protein and analysis of the labeled entities revealed 81% spermidine, 16% putrescine, and 3% spermine. This post-translational modification of a unique protein by attachment of spermidine may be causally connected to the appearance of flower buds in thin-layer tobacco cultures.Polyamines are biologically ubiquitous and have been implicated in many aspects of growth and development in a wide variety of organisms (21)(22)(23) (8,9,16) and Vigna (11), the abnormal flowering habits of polyamine mutants of tobacco (13) After an 8 h period of incubation the tissue was ground in 10% TCA and the pellet washed with 5% TCA until washes were free of radioactivity. The TCA precipitate was then extracted with 0.1 M Na-phosphate (pH 6.8) containing 0.05% SDS, and the volume of the resulting solution reduced by an Amicon Centricon-10 concentrator.…”
mentioning
confidence: 99%
“…Recent evidence suggests a possible role for polyamines, especially Spd,3 in reproductive differentiation in various organisms. The evidence includes regulation by Spd of sporulation in yeast and various filamentous fungi (1,19,23), effects of Spd on differentiation of embryoids in tissue cultures of carrot (8,9,16) and Vigna (11), the abnormal flowering habits of polyamine mutants of tobacco (13) and the accumulation of acylated polyamines in flowering, but not in vegetative tobacco plants (14).…”
mentioning
confidence: 99%
“…Through the use of these inhibitors, it has been demonstrated that ADC is involved in embryo and organ differentiation in plant tissue cultures (Feirer et al, 1984;Tiburcio et al, 1989;Helleboid et al, 1995). PAs, especially their optimal levels, have been implicated in somatic embryogenesis (Feirer et al, 1985;Robie and Minocha, 1989;Sharma and Rajam, 1995), and the altered PA levels have been shown to inhibit this process (Faure et al, 1991). Furthermore, treatments that modify PA levels, such as application of PAs (Altman et al, 1990;Bajaj and Rajam, 1995) or specific PA biosynthesis inhibitors such as DFMA and DFMO (Mengoli et al, 1989;Sharma, 1994), could be used to achieve optimum or improved morphogenesis.…”
mentioning
confidence: 99%